2015
DOI: 10.1148/radiol.14141721
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tissue Complication Probability Model for Radiation-induced Temporal Lobe Injury after Intensity-modulated Radiation Therapy for Nasopharyngeal Carcinoma

Abstract: D1cc is predictive for radiation-induced TLI, suggesting that delivery of a high dose of radiation to a small volume of the temporal lobe is unsafe. A D1cc of 62.83 Gy by using a correction formula for varying fraction size may be the dose tolerance of the temporal lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 11 publications
3
45
2
Order By: Relevance
“…We were, however, able to extract a TD 50 parameter because our model is based on the probit function, which facilitates comparison of results with the more traditional models and analyses. Published values for TD 50 of necrosis/infarction in the brain (the most closely related normal tissue effect for which large amounts of data are reported) for photons are in the range of 60–75 Gy [15,3436]. Our own analysis indicates that, for this set of patients, the TD 50 for voxel image change spans a similar range for typical low proton LET values of 0–2 keV µm −1 .…”
Section: Discussionmentioning
confidence: 62%
“…We were, however, able to extract a TD 50 parameter because our model is based on the probit function, which facilitates comparison of results with the more traditional models and analyses. Published values for TD 50 of necrosis/infarction in the brain (the most closely related normal tissue effect for which large amounts of data are reported) for photons are in the range of 60–75 Gy [15,3436]. Our own analysis indicates that, for this set of patients, the TD 50 for voxel image change spans a similar range for typical low proton LET values of 0–2 keV µm −1 .…”
Section: Discussionmentioning
confidence: 62%
“…Radiation-induced brain injury, including structural and functional deficits, is a severe complication for patients with nasopharyngeal carcinoma (NPC) after radiotherapy (RT) (Zeng, et al, 2015). Based on the onset time of RT, three phases of the pathophysiological reaction to irradiation in normal brain tissue can be classified, acute reaction period (few days to few weeks), early delayed radiation period (1–6 months), and late delayed radiation period (6 months to few years) (Lell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In NPC, many important OARs are adjacent to the edges of the target volumes in the longitudinal direction. Zeng et al (10) established a clinical dose association model and performed an analysis using the equivalent dose in 2-Gy fractions (EQD2), reporting a biologically-equivalent tolerance dose of D 1cc for the development of temporal lobe injury of 62.83 Gy. Hsiao et al (9) reported that patients with NPC showed significant cognitive decline after receiving radiotherapy when the D mean of the temporal lobe was >36 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is an important organ for memory and cognitive function in humans. The control and reduction of radiation dose received by the hippocampus are critical for the quality of long-term survival in patients with NPC who achieve satisfactory therapeutic effects (8)(9)(10). Therefore, to ensure better protection of OARs, clinical planning of HT for NPC often involves using a jaw width of 2.5cm and partly sacrifices the delivery efficiency when using the conventional fixed jaw mode.…”
Section: Introductionmentioning
confidence: 99%